Mobile Cooking Application in Bakery Courses to Improve Soft Skill Competencies - Agustina, Dian; Ingtyas, Fatma Tresno; Sari Waruwu, Mawaddah Azizah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research aims to develop mobile cooking application media in bakery courses to improve soft skill competencies. This research is R&D research. The development model used in this research is the ADDIE (Analysis, Design, Development, Implementation & Evaluating) development model. Validation is carried out by material experts and media experts. The results of the needs analysis carried out on lecturers and students show that the mobile cooking application media is very necessary for learning bread. Material expert validation results obtained 90.5% in the very good category and media expert validation results obtained 95% in the very good category. Limited trials obtained 4.54 in the Very Good category. Field trials obtained 4.46 in the Very Good category. From these data it can be concluded that the mobile cooking application media in bakery courses is very suitable for use in learning. It is hoped that this mobile cooking application can help guide and direct students to practice independently. The implication of this research is that the mobile cooking application can be used by teachers and students to access recipe material precisely and in more detail so that students can build their knowledge independently.